Effects and mechanisms of telmisartan on adiponectin receptors in rat renal proximal tubular epithelial cells induced by high glucose - BU Xi; LIANG Shan-shan; ZHA Dong-qing; CHEN Pei-na; WU Xiao-yan (Linchuang shenzangbing zazhi)
Objective To investigate the effects and mechanisms of telmisartan on expression of adiponectin receptors 1/2 in rat renal proximal tubular epithelial cells induced by high glucose.Methods Cultured rat renal proximal tubular epithelial cells( NRK-52 E) which were synchronized in vitro were divided into 6 groups: normal control group( 5. 5 mmol/L glucose medium culture,24 h),hypertonic control group( 5. 5 mmol/L glucose medium with 19. 5 mmol/L mannitol treatment,24 h),high glucose group( 25 mmol/L glucose medium for 12 h,24 h,48 h,72 h respectively),high glucose +telmisartan group [25 mmol/L glucose medium with different concentrations of telmisartan( 1,10,100 nmol/L) for 24 h],high glucose + telmisartan + GW9662 group( pretreatment with 5 000 nmol/L PPARγ blocker GW9662 for 30 min,then 25 mmol/L glucose and 100 nmol/L telmisartan for 24 h),high glucose + GW9662 group( pretreatment with 5 000 nmol/L PPARγ blocker GW9662 for 30 min,then 25 mmol/L glucose for 24 h). The reverse transcription time-polymerase chain reaction( RT-PCR)and Western blotting were used to detect the expression of adiponectin-receptors 1/2,PPAR-γ mRNA and protein levels in each group. Results In rat renal proximal tubular epithelial cells stimulated by high glucose,telmisartan could promote adiponectin receptors 1/2 expression through the pathway of PPAR-γ. Conclusions In rat renal proximal tubular epithelial cells stimulated by high glucose,telmisartan could promote adiponectin receptor 1/2 expression through the pathway of PPAR-γ.